Exploiting of Natural Resources as Livelihoods of The Border Citizens in The Sebatik Island, North Kalimantan - Brata, Nugroho Trisnu; Wicaksono, Harto; Pramono, Didi (Universitas Negeri Semarang, 2020)
This study aims to discuss social values of political-economic activities in the community that lives in a village located on the state border and to study the narration of the community toward the existence of the state. This research uses a qualitative method, and the data is collected through observation and interview. The research location is in Sungai Limau Village, Sebatik Tengah District, Nunukan Regency, North Kalimantan Province. This paper shows that in Sebatik Island, especially in Sungai Limau Village, there is a change in the environment . There are many banana trees in that village. In the beginning, bananas are considered to have low economic value. But then, there is a creative idea from one of the local people, which is initiating a processed banana. After being processed, bananas turn out to have higher economic value. They see a marketing opportunity in Tawau City, Sabah, Malaysia, across the state border, and it is hard for them to go through the border. For the local people, the state border is no longer considered a ‘sacred area’ and forbidden to enter. Based on the research, it can be concluded that the environment may seem to have limitations in fulfilling people's needs, but then, there is actually hidden potential of natural resources that can be processed to meet their needs.